MARKET ANALYSIS OF COUNTRIES ALONG THE FLAVIA CORRIDOR (Perner's Contacts, 2012)
This article belongs to the publicity of European project FLAVIA. Its goal is in summary of main market actors and areas in involved countries with a special impact to Czech Republic. All goals are summarized at the end of the article.
Keywords: FLAVIA, market actor, economic cluster